1986
DOI: 10.1177/004051758605601009
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cross-Sectional Area, Perimeter, Circularity, and Secondary Wall Thickness of Different Cotton Fibers During Growth

Abstract: Bolls from four cottons, one from each of the cultivated species G. arboreum, G. herbaceum, G. barbadense, and G. hirsutum, were picked at weekly intervals. Crosssectional area and perimeter were determined for 200 fibers of each of these samples, and secondary wall thickness and circularity were calculated. Cross-sectional area, circularity, and secondary wall thickness increased with fiber growth. These increases were greater in the initial stages of development than in the later stages. The percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…7 to 10 times) and smaller sample sizes (n ¼ 200). Chauhan et al 52 also measured the cross-sectional properties of various cotton genotypes using a similar method to Petkar et al 21 (and the same sample number) at 45, 55, and 65 DPA stages of development. The Chauhan et al 52 results were similar, except that increases in fiber perimeter with increasing developmental age were detected.…”
Section: Effects Of Genotype and Defoliation Timingmentioning
confidence: 99%
“…7 to 10 times) and smaller sample sizes (n ¼ 200). Chauhan et al 52 also measured the cross-sectional properties of various cotton genotypes using a similar method to Petkar et al 21 (and the same sample number) at 45, 55, and 65 DPA stages of development. The Chauhan et al 52 results were similar, except that increases in fiber perimeter with increasing developmental age were detected.…”
Section: Effects Of Genotype and Defoliation Timingmentioning
confidence: 99%
“…The degree of cell wall thickening for ir with an average ginned weight of I or 2 mg showed the capacity for cell wall synthesis was not termin with the termination of embryo. growth, since cm growth most likely terminated prior to 16 duys I anthesis when cellulose deposition becomes prom in fiber, fuzz, and seed epidermal cells ~:~, I I. Although fiber length was similar in r~r~r.…”
Section: Ginned Seed Weight Distributions and Fiber Propertiesmentioning
confidence: 99%
“…A cross-sectional analysis of G. (irboretim, G. herceum. G. barbadense, and G. hir.sutum fiben during the iod of cell wall thickening showed that increases in cell ll thickness paralleled increases in circularity ( 16]. High ndard deviations in perimeter measurements obscured V trends related to the chronological age of fibers [ 16].…”
mentioning
confidence: 99%
See 2 more Smart Citations